Prediction of Minocycline Activity in the Gut From a Pig Preclinical Model Using a Pharmacokinetic -Pharmacodynamic Approach - Vallé, Quentin; Roques, Béatrice B.; Bousquet-Mélou, Alain; Dahlhaus, David; Ramon-Portugal, Felipe; Dupouy, Véronique; Bibbal, Delphine; Ferran, Aude A. (Frontiers in Microbiology, 2021)
The increase of multidrug-resistant (MDR) bacteria has renewed interest in old antibiotics, such as minocycline, that can be active against various MDR Gram-negative pathogens. The elimination of minocycline by both kidneys and liver makes it suitable for impaired renal function patients. However, the drawback is the possible elimination of a high amount of drug in the intestines, with potential impact on the digestive microbiota during treatment. This study aimed to predict the potential activity of minocycline in the gut after parenteral administration, by combining in vivo and in vitro studies. Total minocycline concentrations were determined by UPLC-UV in the plasma and intestinal content of piglets following intravenous administration. In parallel, the in vitro activity of minocycline was assessed in sterilized intestinal contents and compared to its activity in a standard broth. We found that minocycline concentrations were 6–39 times higher in intestinal contents than plasma. Furthermore, minocycline was 5- to 245-fold less active in large intestine content than in a standard broth. Using this PK-PD approach, we propose a preclinical pig model describing the link between systemic and gut exposure to minocycline, and exploring its activity against intestinal bacteria by taking into account the impact of intestinal contents.